Evaluation of the Training on Trainers of Education for Earthquake Preparedness and Trauma Healing for ASPNet Teachers in Bantul, Yogyakarta Special Territory - Nahiyah Jaidi Faraz (JOURNAL OF EDUCATION, 2009)
This study aims to describe disaster preparedness and trauma healing programs from the context, input, process, and product aspects. The context refers to the appropriateness of the program design, the input to resources in the program, the process to the accomplishment of the program, and the product to impacts and benefits of the program. This study was an evaluation research study. The subjects were 105 teachers from 34 schools in Bantul Regency consisting of art, guidance and counseling, and religion teachers. The data were collected using questionnaires and were analyzed using the content analysis on the training materials and other relevant documents. The results show that the program is relevant to the needs in relation to trauma healing and disaster preparedness. The materials of the training help the participants understand trauma healing and disaster preparedness. According to the participants, the training is effective although the materials need to be synchronized. The trainers have been applying and spreading out the result of the training although only few of them have already developed the materials.